Integration of core hopping, quantum-mechanics, molecular mechanics coupled binding-energy estimations and dynamic simulations for fragment-based novel therapeutic scaffolds against Helicobacter pylori strains. (December 2019) - Pasala, Chiranjeevi; Katari, Sudheer Kumar; Nalamolu, Ravina Madhulitha; Aparna, R. Bitla; Amineni, Umamaheswari
Graphical abstract: Highlights: Experimental inhibitors were utilized for shape-screening using in-house library. Substitutability endpoints of new scaffolds were determined by scaffold hopping method. Prediction accuracy was enhanced by HTVS, RRD, QPLD, ADMET and IFD programs. Specific consistency of molecular complexes was elucidated by long-range MD simulations. Salient interaction profiles of the eight scaffolds potentiate as novel chemical moieties. Abstract: The cascade of complications by Helicobacter pylori including extra-gastric and peptic ulcers to gastric cancer imposes a salient cause of cancer death globally. Adverse drug reactions and burgeoned genetically diverse resistant strains create a big barrier in the treatment, thereby demanding novel proof-of-concept ligands and breakthrough medicines. Hence, as a follow-up of the previous proteomics study against 53 H. pylori strains, KdsB was identified as a vital conserved-target enzyme. Herein, the rational therapeutic-design strategies exploiting for such a hidden cryptic inhibitor were utilized in lead-optimization campaigns through shape screening, the powerful scaffold-hopping, rigid-receptor, quantum-polarized ligand and induced-fit docking techniques coupled with estimating molecular-mechanics energies (Δ G bind ) through generalized-Born and surface-area-continuum solvation. Variable-dielectric-Surface-Generalized Born, a novel energy model and physics-based corrections for bond-interactions and ADME/Tox predictions led to yield improved eight therapeutic chemical entities with positive synthesizability scores (0–1). Long-range molecular dynamics (300 ns) simulations revealed stability of leads. Significant computational findings with better competitive binding-strengths than experimental ligands could pave the best choice for selecting better leads as it warrants and filter false-positives based on the consensus of scaffolds interactions and suggesting that designed novel class of KdsB-antagonist molecules may dysfunction the target and stimulate new insights for developing effectual medical interventions.